Puding Berbahan Ikan Mujair dan Tepung Kacang Hijau Sebagai Alternatif Makanan Selingan Untuk Pencegahan Balita Stunting - Setiawati, Dina; Hadiningsih, Naning; Karimah, Ima (Universitas Djuanda, 2023)
Stunting is a major nutritional problem in Indonesia, where its prevalence reached 21.6% based on the results of the 2022 Indonesian Nutrition Status Survey. Stunting prevention is much more effective than stunting treatment. Therefore, providing food, especially food from animal protein sources, is an effective intervention to improve the nutritional status of children under five and prevent stunting. Tilapia fish and green beans are types of food with quite high levels of protein, iron and zinc compared to similar foods. In general, children like sweet snacks such as pudding. Besides that, pudding is also a snack that is very easy to make. The aim of this research is to formulate and conduct organoleptic tests of pudding made from tilapia fish and green bean flour as an alternative distraction for stunted toddlers. The type of research used was experimental research, namely a pudding formulation made from tilapia fish and green bean flour. Next, organoleptic tests were carried out on 25 trained panelists to determine acceptability and which formula was most preferred. The research results showed that there were three pudding formulas with a ratio of tilapia fish and green bean flour, namely F1 (13%: 6.5%), F2 (18%: 9%) and F3 (23%: 11.5%). Of the three formulas, F1 is the most preferred pudding in terms of color and taste, while F2 is the most preferred in terms of aroma and texture, but overall F1 is the pudding formula that is most liked by the panelists.